Teacher retention in crisis: Informing policy to keep Ghanaian educators in classrooms - Richard Lionel Gorni; Diding Nurdin; Johar Permana; Djaman Satori (Inovasi Kurikulum, 2024)
Ghana's schools face a severe teacher retention crisis, with only 36 percent of teachers in a district survey planning to stay in their roles. Researchers conducted a comprehensive survey of 138 teachers to investigate their reasons for wanting to leave the profession. Common themes emerged, including low pay, poor working conditions, and overwhelming workloads. Additionally, concerns about teacher well-being and the declining status of the teaching profession were highlighted as significant issues. The study sought to identify strategies to keep teachers engaged, employing a theory about employee turnover to guide the analysis. Researchers carefully examined the survey responses and pinpointed key strategies to address the crisis. These included reducing teacher workloads, improving working conditions, and enhancing the prestige and status of the teaching profession. This research provides valuable insights for policymakers seeking effective solutions to Ghana's teacher retention problems. The findings underscore the urgent need to address the factors driving teachers away and implement strategies to maintain a stable, motivated, and highly skilled teaching workforce, which is crucial for advancing Ghana's educational system.